An examination of Roy Bhaskar's critical realism as a basis for educational practice. Issue 1 (1st January 2021) - Mirzaei Rafe, Mehri; Noaparast, Khosrow Bagheri; Hosseini, Afzal Sadat; Sajadieh, Narges
ABSTRACT: This article is an up-dated version of Gordon Brown's ontological approach to education. It tests the hypothesis that Roy Bhaskar's critical realism can successfully underpin education by applying it to: (1) curriculum; (2) pedagogy; and (3) assessment. It argues that critical realism provides an inter-disciplinary praxis, built around science, sociology and metaphysics, which can be taken up by educationalists to enhance their agency and produce positive knowledge cultures in their every day practices. Therefore Bhaskar's critical realism can unify those streams of educational thought that tend to create divisions which impede the development of knowledge cultures, and limit agency.